2022
DOI: 10.3390/ijms23052851
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Musashi-1 and Musashi-2 Double Knockdown on Notch Signaling and the Pathogenesis of Endometriosis

Abstract: The stem cell marker and RNA-binding protein Musashi-1 is overexpressed in endometriosis. Musashi-1-siRNA knockdown in Ishikawa cells altered the expression of stem cell related genes, such as OCT-4. To investigate the role of both human Musashi homologues (MSI-1 and MSI-2) in the pathogenesis of endometriosis, immortalized endometriotic 12-Z cells and primary endometriotic stroma cells were treated with Musashi-1- and Musashi-2-siRNA. Subsequently, the impact on cell proliferation, cell apoptosis, cell necros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
(86 reference statements)
1
10
0
Order By: Relevance
“…It is in agreement with (and extends beyond) the limited number of previous studies evaluating the role of Musashi-1 in endometrial cancer: Previous work showed that Musashi-1 is overexpressed in endometrial cancer [16] and high expression is prognostically unfavorable [18]. Msi-1 has also been demonstrated to be overexpressed in endometrial stem cells [35] and to be associated with stem cell pathways both in endometrial cancer [17] and endometriosis [67]. Finally, Musashi-1 has been identified as a potential therapeutic target in other malignancies, including breast cancer [15] and glioblastoma [68] and here, we report an in-depth evaluation of its targeting in endometrial cancer.…”
Section: Discussionsupporting
confidence: 90%
“…It is in agreement with (and extends beyond) the limited number of previous studies evaluating the role of Musashi-1 in endometrial cancer: Previous work showed that Musashi-1 is overexpressed in endometrial cancer [16] and high expression is prognostically unfavorable [18]. Msi-1 has also been demonstrated to be overexpressed in endometrial stem cells [35] and to be associated with stem cell pathways both in endometrial cancer [17] and endometriosis [67]. Finally, Musashi-1 has been identified as a potential therapeutic target in other malignancies, including breast cancer [15] and glioblastoma [68] and here, we report an in-depth evaluation of its targeting in endometrial cancer.…”
Section: Discussionsupporting
confidence: 90%
“…Filipchiuk et al found increased expression of the BIRC5 gene in the peripheral blood of women with endometriosis, indicating a role in cell proliferation and anti‐apoptotic activity in the development of the disease 58 . Besides, Strauß et al demonstrated that stem cell marker and RNA‐binding protein Musashi‐1 have an impact on Notch signaling and the pathogenesis of endometriosis through the downregulation of proliferation, stemness characteristics and the upregulation of apoptosis 59 . These previous studies and our study consistently reveal critical roles for dysregulated proliferation and apoptosis in the pathogenesis of endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…According to retrograde menstruation theory, to develop endometriosis, live endometrial cells migrate through the fallopian tubes and are implanted on the surface of the pelvic cavity [6, 43], indicating that the ability of endometrial cell migration and invasion is also important for the establishment of ectopic lesions. The ability of migration and invasion, which is being studied in endometriosis by many studies, is also the biological behavior of endometriotic cells, which is similar to malignant cells [44, 45]. Therefore, in this study, in addition to the effect of BIBR1532 on cell proliferation, its effects on cell migration and invasion were also tested.…”
Section: Discussionmentioning
confidence: 99%